Recent Advances in AI: Exploring the Impact of GPT-4 and Beyond - Anjaneyulu Prabala Sriram, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This article examines the transformative impact of GPT-4 on artificial intelligence, focusing on its architectural innovations, technical capabilities, and industry applications. The article encompasses GPT-4's advancements in code understanding, healthcare applications, and multimodal processing capabilities. Through comprehensive evaluation of its performance across various domains, we explore both the model's achievements and current limitations. The article examines computational efficiency challenges, temporal reasoning capabilities, and reliability concerns while discussing future research directions in architecture evolution and training methodologies. Our findings indicate that while GPT-4 represents a significant leap forward in AI technology, addressing key challenges in efficiency and knowledge integration will be crucial for future development.
Keywords: Large Language Models; Artificial Intelligence; Neural Architecture; Multimodal Processing; Machine Learning